Dosimetric impact of deformable image registration using radiophotoluminescent glass dosimeters with a physical geometric phantom. Issue 4 (7th January 2023) - Sakulsingharoj, Siwaporn; Kadoya, Noriyuki; Tanaka, Shohei; Sato, Kiyokazu; Nakamura, Mitsuhiro; Jingu, Keiichi
Abstract: Purpose: To study the dosimetry impact of deformable image registration (DIR) using radiophotoluminescent glass dosimeter (RPLD) and custom developed phantom with various inserts. Methods: The phantom was developed to facilitate simultaneous evaluation of geometric and dosimetric accuracy of DIR. Four computed tomography (CT) images of the phantom were acquired with four different configurations. Four volumetric modulated arc therapy (VMAT) plans were computed for different phantom. Two different patterns were applied to combination of four phantom configurations. RPLD dose measurement was combined between corresponding two phantom configurations. DIR‐based dose accumulation was calculated between corresponding two CT images with two commercial DIR software and various DIR parameter settings, and an open source software. Accumulated dose calculated using DIR was then compared with measured dose using RPLD. Results: The mean ± standard deviation (SD) of dose difference was 2.71 ± 0.23% (range, 2.22%–3.01%) for tumor‐proxy and 3.74 ± 0.79% (range, 1.56%–4.83%) for rectum‐proxy. The mean ± SD of target registration error (TRE) was 1.66 ± 1.36 mm (range, 0.03–4.43 mm) for tumor‐proxy and 6.87 ± 5.49 mm (range, 0.54–17.47 mm) for rectum‐proxy. These results suggested that DIR accuracy had wide range among DIR parameter setting. Conclusions: The dose difference observed in our study was 3% for tumor‐proxy and within 5% for rectum‐proxy. The custom developed physical phantom with inserts showed potential for accurate evaluation of DIR‐based dose accumulation. The prospect of simultaneous evaluation of geometric and dosimetric DIR accuracy in a single phantom may be useful for validation of DIR for clinical use.